Deconstruction of the modern subject by Arendt and Levinas: the other and politics - Yılmaz, Selbin. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2014., 2014)
This thesis examines the notion of subjectivity in the philosophies of Hannah Arendt and Emmanuel Levinas. It argues that the terms of the dichotomy between the modern and post-modern conceptualizations of the subjectivity are not satisfying for Arendt and Levinas. It aims to show that we do not have to make a choice between the self-sovereign and autonomous subject and the subjected subject. Arendt and Levinas have deconstructed the modern subject without subjugating it to any other structure, discourse or hegemonic process according to which the subject is neither at the exact center of all possible action nor is completely passive with having no capacity to act. In this respect, the study explores how Arendt and Levinas conceptualize subjectivity as „subject in plurality‟ through integrating the other into the conceptualization. The major concern of this thesis is to question the possibility of collocating Arendt and Levinas in terms of their conceptualization of subjectivity in the context of how can they help us to reconceptualize politics. Despite the existence of some radical disjunctions in their theories, this thesis claims that they have still significant common points that make engaging them in a dialogue possible. The conclusion reached is that although they follow completely different ways when developing their philosophies, at the end, they reach to a similar conclusion which proposes that the subjectivity is dependent upon the existence of the others.